Q: How do you solve x - 4y 10?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

How do you solve 4y plus x equals 8

Assume the expression is x = 40 - 4y, and assume we want to solve for y. Rearrange the terms to get: x - 40 = -4y y = -¼(x - 40)

2

Assume the expression is x = 40 - 4y, and assume we want to solve for y. Rearrange the terms to get: x - 40 = -4y y = -¼(x - 40)

x + y = 10. Substitute x = 4y into this equation: 4y + y = 10 Combine like ters: 5y = 10 Divide through by 5: y = 2 Substitute this value of y in x = 4y ie x = 4*2 = 8.

Related questions

How do you solve 4y plus x equals 8

Assume the expression is x = 40 - 4y, and assume we want to solve for y. Rearrange the terms to get: x - 40 = -4y y = -¼(x - 40)

2

The answer to x2 - 2x - 4y2 - 4y =(x - 2y)(x - 2y - 2)

If by "What is the answer to", you mean "How do you factor", then we can solve it as follows: x2 + 13xy + 36y2 = x2 + 4xy + 9xy + 36y2 = x(x + 4y) + 9y(x + 4y) = (x + 9y)(x + 4y)

2x - 3y = -4x + 4y = -9from the second equation x = -9-4y , substitute it in the first equation.2(-9-4y)- 3y= -4-18-8y-3y = -4-18-11y = -4-11y = -4+18-11y = 14y = -14/11now, solve for x :x = -9-4yx = -9-4(-14/11)x = -43/11

x + y = 10. Substitute x = 4y into this equation: 4y + y = 10 Combine like ters: 5y = 10 Divide through by 5: y = 2 Substitute this value of y in x = 4y ie x = 4*2 = 8.

x = 4y - 2x = 6y + 84y - 2 = 6y + 8Subtract 4y from each side:-2 = 2y + 8Subtract 8 from each side:-10 = 2yDivide each side by 2:-5 = yx = 4y - 2x = -22

There are infinite solutions, since you have 2 unknowns and 1 equation. x+4y=12 4y=12-x y=3-0.25x or x=12-4y If you choose an y or an x, the other is defined.

i dont know what you are trying to solve for, but if you are solving for x and y. u have to...... 3x-4y=4 x= 4/3..... 1.33 y=4/-4...... -1

Someone's homework? This is a pair of simultaneous equations: 1) 3x - 4y = 10 2) y = x - 3 Substituting for y in equation 1: 3x - 4(x-3) = 10 3x - 4x + 12 = 10 -x + 2 = 0 -x = -2 x = 2 substitute into equation 2: y = 2 - 3 y = -1